2004
DOI: 10.1262/jrd.50.381
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Ovarian Development in the Prepubertal Antarctic Minke Whale (Balaenoptera bonaerensis)

Abstract: Abstract. This study describes the morphological and morphometrical changes associated with prepubertal ovarian development in the Antarctic minke whale (Balaenoptera bonaerensis). Ovaries were harvested from 94 immature minke whales caught in the Antarctic Ocean during the summer feeding season (December-March). Notable differences in ovarian size and morphology were found among animals. Up to 10 folds difference in ovarian weight was found among prepubertal whales of similar body size. During the prepubertal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…We found no significant weight asymmetry between right and left immature bowhead ovaries, in contrast to Tetsuka et al () who reported that the right ovary was three times as likely to be the heavier ovary in a pair for sexually immature Antarctic minke whales.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found no significant weight asymmetry between right and left immature bowhead ovaries, in contrast to Tetsuka et al () who reported that the right ovary was three times as likely to be the heavier ovary in a pair for sexually immature Antarctic minke whales.…”
Section: Discussioncontrasting
confidence: 99%
“…Chittleborough () similarly found little change in ovary weights during the earlier prepubertal period of humpback whales, but found that weights began increasing as puberty approached, albeit with greater variation in ovary weights relative to body length. Tetsuka et al () also noted a lack of consistency in ovary weights within immature body length classes, with 10‐fold differences in ovary weights among recently weaned Antarctic minke whale calves (<6 m in length) and sixfold differences in ovary weights among prepubertal Antarctic minke whales (∼8 m in length). Still, they reported that ovary weights approximately doubled overall during the course of prepubertal development (6–7 years), which we did not find in immature bowheads.…”
Section: Discussionmentioning
confidence: 99%
“…Eschrichtius robustus joints are all open at birth and closed before the animal reaches 7 months of age. The approximate total body length for E. robustus at the age of 7 months old (700 cm) (Muranishi et al, 2004; Tetsuka et al, 2004) and that for B. physalus at the age of 6 months old (1,100 cm) (Ohsumi et al, 1958; Mizroch et al, 1984) are available in the literature, but age/length estimates less than 1 year old have not been established for the other two species. All of the joints in B. acutorostrata and M. novaeangliae are closed by the age of 1 year and are at a stable joint ossification stage that does not progress further during the life of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…1): Eschrichtiidae: Eschrichtius robustus (gray whale); Balaenopteridae: Balaenoptera acutorostrata (minke whale), Balaenoptera physalus (fin whale), and Megaptera novaeangliae (humpback whale). These species range in size from 8 m to 27 m in total body length at physical maturity (Omura, 1953; Blokhin and Vladimirov, 1983; Mizroch et al, 1984; Muranishi et al, 2004; Tetsuka et al, 2004). Growth to these large sizes requires alteration of nutrient allocation while adapting to lifestyle changes.…”
mentioning
confidence: 99%
“…Hunters were trained by USFWS personnel and given field notebooks to document each animal hunted. Sexual maturity was determined by presence of a CL within the ovary [36][37][38][39]. Ovaries indicated if the female was reproductively active during her current cycle by presence of the CL, whereas ovaries lacking a CL were termed inactive.…”
Section: Sample Collectionmentioning
confidence: 99%